2015
DOI: 10.4103/0976-9668.149072
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition among under-five children in India and strategies for control

Abstract: Malnutrition among under-five children is an important concern for the health authorities in India. The aim of the present review was to assess the burden of under-nutrition and over-nutrition, its determinants and strategies required to tackle malnutrition among under-five children in India. Recent data were collected from Google search, Medline, and others. The information retrieved was reviewed and analyzed for discrepancies. Existing evidence shows that the prevalence of under-nutrition among under-five ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 24 publications
4
89
1
3
Order By: Relevance
“…2017; 6(3):e14176. on Indian children, all anthropometric indices indicated an unfavorable position for children in this region (18). The results of most studies conducted in this field represent high levels of chronic malnutrition among children, which is of high concern and should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…2017; 6(3):e14176. on Indian children, all anthropometric indices indicated an unfavorable position for children in this region (18). The results of most studies conducted in this field represent high levels of chronic malnutrition among children, which is of high concern and should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Following findings were noted in this review, underweight: 39-75%, stunting: 15.4-74%, wasting: 10.6-42.3%. 25 A recent study which was conducted among children in the age group of 3 months to 3 years in 130 districts through demographic and health surveys in 53 countries over a period of 1986 to 2006 found that the variance in the mild underweight has a larger and more robust correlation with child mortality than the variance in severe under-weight. The study also concluded that the prevalence of mild under-weight deserves greater attention than the severe under-weight and also stated it to be a useful signal of changing public health conditions among preschool children in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…1 It occurs particularly in weaklings and children in the first years of life. It is not only an important cause of childhood morbidity and mortality, but leads also to permanent impairment of physical and possibly, of mental growth of those who survive.…”
Section: Introductionmentioning
confidence: 99%